The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/bmc.3789
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of four antiepileptic drugs in human plasma samples using an ultra‐high‐performance liquid chromatography tandem mass spectrometry method and its application in therapeutic drug monitoring

Abstract: Therapeutic drug monitoring of antiepileptic drugs is widely practiced to achieve optimal efficacy and avoid adverse side effects. We describe an ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC/MS/MS) method developed for the monitoring of four frequently prescribed antiepileptic drugs - lamotrigine, levetiracetam, oxcarbazepine and topiramate. The main pharmacologically active metabolite of oxcarbazepine (mono-hydroxy-derivative metabolite, MHD) was also quantified. After addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
(28 reference statements)
0
13
1
Order By: Relevance
“…When the results of the developed and validated method were compared to those obtained using high performance liquid chromatography (HPLC), HPTLC and gas chromatography, there were no significant difference in the accuracy and precision, the only limitation was that the LOQ and LOD were higher in the present study as compared to those obtained using the HPLC method. The lowest LOQ in HPLC documented in literature was approximately 0.1 µg/ml [18,19] while in the present study, it was 3.15 µg/ml. However, the LOQ of this HPTLC method is well below the therapeutic range, which is 10 to 40 µg/ml and therefore, could be used reliably to carry out therapeutic drug monitoring.…”
contrasting
confidence: 63%
“…When the results of the developed and validated method were compared to those obtained using high performance liquid chromatography (HPLC), HPTLC and gas chromatography, there were no significant difference in the accuracy and precision, the only limitation was that the LOQ and LOD were higher in the present study as compared to those obtained using the HPLC method. The lowest LOQ in HPLC documented in literature was approximately 0.1 µg/ml [18,19] while in the present study, it was 3.15 µg/ml. However, the LOQ of this HPTLC method is well below the therapeutic range, which is 10 to 40 µg/ml and therefore, could be used reliably to carry out therapeutic drug monitoring.…”
contrasting
confidence: 63%
“…The first study was reported by Carlow, Shi, and Schofield (). The second study was reported by Julien Dupouey, Doudka, Belo, Blin, and Guilhaumou (). Both studies were efficient for the determination of the AED.…”
Section: Introductionmentioning
confidence: 93%
“…1,2 The pharmacotherapy with AEDs is the first choice for the treatment of epilepsy as it controls the occurrence of unpredictable epileptic seizures on approximately two thirds of the patients. 3 Approximately 30-40% of patients do not achieve seizure control with a single AED and rational polytherapy with the goal of finding combinations of AEDs that have favorable characteristics, has become of greater importance. 4 Before that one should ensure that the drug has reached its therapeutic range and there is no possibility to increase its daily dose.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their narrow therapeutic range in adults (10-40 µg mL -1 , 5-20 µg mL -1 and 2-12 µg mL -1 , respectively for PB, PHT and CBZ) 5 and their complex pharmacokinetic properties, their blood levels should be monitored. Therapeutic ranges of PB, PHT and CBZ in children are 20-60 µg mL -1 , 3 6-11 µg mL -1 6 and 4-12 µg mL -1 , 7 respectively. Lethal concentrations of PB and PHT are 50 µg mL -1 for both drugs 5 and fatalities could be observed in CBZ serum concentrations of >20 µg mL -1 5 or >39 µg mL -1 .…”
Section: Introductionmentioning
confidence: 99%